Morphological description of infective larval stage of Physaloptera (Spirurida: Physalopteridae), and histological lesions in the paratenic host Leptodactylus macrosternum (Anura: Leptodactylidae) in Caatinga biome, Brazil - Gabriela Felix-Nascimento; Fabiano M. Vieira; Ellen C. A. Gomes; Ana Catarina L. Albinati; Luís C. Muniz-Pereira; Geraldo J. B. Moura; Leonardo B. Ribeiro; Jaqueline B. Oliveira (Revista Mexicana de Biodiversidad)
The present study aimed to describe the infective larval stage of Physaloptera sp. parasitizing Leptodactylus macrosternum and the microscopic lesions of these larvae in the stomach wall. Forty-five specimens of L. macrosternum were collected during the rainy season in May 2018, in the municipality of Petrolina, sub-middle São Francisco region, state of Pernambuco, Brazil. Twenty-seven infective larval stage (L3) specimens of Physaloptera sp. were collected attached in the stomach mucosa of 11 specimens (24.4%) of L. macrosternum. No other larval stages (L4) or adult of Physaloptera was found among the necropsied hosts. The stomach’s L3 attachment site showed macroscopic and histological lesions such as hyperaemic and ulcerated sites, mucous tunic necrotic regions, and inflammatory infiltrate eosinophilic. This is the first morphological study of Physaloptera infective larvae parasitizing L. macrosternum, and the first record of this paratenic host in the Caatinga biome. Additionally, it is also the first histopathological study of lesions caused by infective larvae of Physaloptera in this host species.